Syngas obtainment from the gasification of asphaltenes of the San fernando crude oil - Afanador Rey, Luz Edelmira; Grosso Vargas, Jorge Luis; Moreno Arciniegas, Laura Smith; Rodríguez Corredor, Fabio Ernesto (CT&F - Ciencia, Tecnología y Futuro, 2009)
In this work, we developed the first study in Colombia to obtain and evaluate syngas compositions derived from asphaltenes gasification. These asphaltenes came from the implementation of a Deasphalting process to San Fernando crude oil, with the purpose of looking for technological options for their utilization. We performed the design, installation and commissioning of facilities for the gasification of asphaltenes at laboratory scale, it following an experimental methodology, performing nine tests and considering temperature and agent gasification quantity (oxygen) as independent variables. The syngas derived from gasification was analyzed by two chromatographic techniques, which reported the presence of refinery gases and sulfur. We evidenced a growth tendency of CO, H2 and sulfur composition and a decrease in CH4 and CO2 composition with temperature. The composition of the syngas was evaluated with different quantities of gasification agent (33%, 40% and 47% the amount of oxygen theoretically required for complete combustion) at each temperature levels operated. It was established that when using a 40% of gasification agent, you get greater average content of CO and H2, which are the interest gases in the gasification process.